Лінійна система диференціальних рівнянь з точкою звороту - Ключник, І.Г. (Український математичний журнал, 2010)
Система линейных дифференциальных уравнений с малым параметром при части производных сводится к каноничной форме, а также изучаются свойства матрицы преобразования. A system of linear differential equations with small parameter as a coefficient of a part of derivatives is reduced to the canonical form and the properties of the transformation matrix are investigated.